Gas phase catalytic oxidation of VOCS using hydrothermally synthesized nest-like K-OMS 2 catalyst - M.D. de Luna,; J.M. Millanar,; A. Yodsa-Nga,; K. Wantala, (Universiti Kebangsaan Malaysia, 2017)
Toluene and benzene are hazardous air pollutants commonly found in the atmosphere at relatively high concentrations. Due to this, a need to remove these pollutants became a necessity. In this study, octahedral molecular sieve type manganese oxide (K-OMS 2) prepared by hydrothermal method was utilized to decompose toluene and benzene. X-ray diffraction (XRD), scanning electron microscopy (SEM), Brunauer-Emmet-Teller (BET), X-ray absorption near edge structure (XANES) analysis were used to investigate the crystallinity, morphology, surface area and oxidation state of K-OMS 2, respectively. It was confirmed that K-OMS 2 was successfully produced from hydrothermal method. Central composite design (CCD) was used to investigate the main and interaction effects of gas hourly space velocity (GHSV) and reaction temperature on the thermal catalytic oxidation of benzene and toluene. Both factors were found to have significant main and interaction effects on toluene oxidation. However, only the main effects of the factors were significant for benzene. This result was due to the difference in the stability of the structures of the two VOCs. The K-OMS 2 obtained has excellent efficiency on toluene and benzene removal. Toluene was completely decomposed at a temperature as low as 250°C while benzene decomposition reached around 98% at 292.4°C.